2013
DOI: 10.1590/s0103-21002013000400004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da fragilidade de idosos institucionalizados

Abstract: Objective: To assess the presence of frailty and its relationship to sociodemographic and clinical characteristics in institutionalized elderly. Methods: Cross-sectional study with 54 elderly residents in long-stay institutions in the Northeast of Brazil. The data collection instruments were the Edmonton Frail Scale, socioeconomic assessmentand health profiles. Data were analyzed using descriptive statistics and Chi-square test, with significance level of 0.05. Results: The mean age was 72.4 (± 8.5) years, 61.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0
29

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 6 publications
3
14
0
29
Order By: Relevance
“…These instruments have demonstrated acceptable reliability as well as a concurrent, predictive and good validity (17) . The results of this study confirm higher frequency of frailty as age increases, being more prevalent among the advanced age elderly; similar data have been found in other studies (6,13) . During the aging process, there is a gradual decrease of physiological reserve and consequent decline accumulated in several physiological systems, resulting in the condition of frailty 7) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These instruments have demonstrated acceptable reliability as well as a concurrent, predictive and good validity (17) . The results of this study confirm higher frequency of frailty as age increases, being more prevalent among the advanced age elderly; similar data have been found in other studies (6,13) . During the aging process, there is a gradual decrease of physiological reserve and consequent decline accumulated in several physiological systems, resulting in the condition of frailty 7) .…”
Section: Discussionsupporting
confidence: 92%
“…However, in studies using EFS, prevalence of fragility in the elderly who lived in the community was 39.1% in Ribeirão Preto, São Paulo (11) and 41.3% in Montes Claros, Minas Gerais (6) , while in the elderly assisted by the Family Health Strategy in Embu, São Paulo, it was 30.1% (12) . Prevalence of frailty was 74.1% in the elderly of an institution of long permanence in Fortaleza, Ceará (13) ,while it was 95.2% in the elderly hospitalized in the Medical Clinic of the Emergency Department of a University Hospital of Ribeirão Preto, São Paulo (14) . We observed that different conditions may influence the prevalence of frailty in the elderly.…”
Section: Discussionmentioning
confidence: 93%
“…This result may be due to the place of study, a FHU, since independent people with functional capacity preserved seek most frequently FHUs. Others also had similar percentages [2,4,7,8,10,12,13], diverging from other researches that worked with the same object, but in the hospital context [3,6,11], as well as at a Long-Term Permanence Institution for the elderly (LTPI) [16,18], where there was a greater predominance of frailty in the participants, and where there are elderly individuals with comorbidities, cognitive deficits and functional decline [11].…”
Section: Discussionmentioning
confidence: 84%
“…Although frailty does not always relate to the consequences of chronic diseases in the elderly, or vice versa, they may associate with each other, indicating a high risk for events that are harmful to health [18]. Through the results, the frailty associated with heart disease, diabetes mellitus, osteoporosis, respiratory diseases, urinary tract infection and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation